PRICE SETTING DAN MANAJEMEN OPERASIONAL YANG DITERAPKAN DALAM KEBUDAYAAN MINANGKABAU (STUDI PADA USAHA RUMAH MAKAN PADANG) - Muhammad Aufa (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this study is to explore how to setting the sale prices and operational management which applied at Padang restaurant where the owner is Minangkabau ethnicity or mix Minangkabau ethnicity. The study is conducted with etnomethodology. The study show three uniqueness on price setting which applied on Padang restaurant (1) Production cost, where one of them is really considered by owner of Padang restaurant, that is spice.  (2) Payroll, where some Padang restaurant using mato system on their payroll. (3) Zakat, applied on price setting in Padang restaurant and as duty for every moslem. Based on 3 uniqueness show Minangkabau special setting the price is Minangkabau price setting. Key word : Minangkabau culture, prices, operational management, Padang restaurant